2005
DOI: 10.1111/j.0022-202x.2005.23624.x
|View full text |Cite
|
Sign up to set email alerts
|

Redox Imbalance Induced by Contact Sensitizers Triggers the Maturation of Dendritic Cells

Abstract: Although p38 mitogen-activated protein kinases (MAPK) play a crucial role in the activation of monocyte-derived dendritic cells (MoDC) by contact sensitizers, the upstream signals of p38 MAPK remain undetermined. To examine whether sensitizers induce redox or oxidative stress in dendritic cells (DC), which subsequently stimulate p38 MAPK, we measured the ratio of the oxidized (GSSG) versus reduced (GSH) form of cellular glutathione in MoDC stimulated with five sensitizers including NiCl2 and 2,4-dinitrochlorob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 38 publications
2
69
0
Order By: Relevance
“…In previous results performed with the foetal skin-derived dendritic cell line (FSDC), we reported that DNFB activates p38 MAPK and ERK1/2 via the production of reactive oxygen species and that protein oxidation plays an important role in MAPKs activation (Matos et al, 2005b). These results are in agreement with the key role of oxidative stress in the activation of MAPKs (Mizuashi et al, 2005;Hirota et al, 2009;Suzuki et al, 2009;Kagatani et al, 2010).…”
Section: Activation Of the Mitogen-activated Protein Kinases (Mapks)supporting
confidence: 87%
“…In previous results performed with the foetal skin-derived dendritic cell line (FSDC), we reported that DNFB activates p38 MAPK and ERK1/2 via the production of reactive oxygen species and that protein oxidation plays an important role in MAPKs activation (Matos et al, 2005b). These results are in agreement with the key role of oxidative stress in the activation of MAPKs (Mizuashi et al, 2005;Hirota et al, 2009;Suzuki et al, 2009;Kagatani et al, 2010).…”
Section: Activation Of the Mitogen-activated Protein Kinases (Mapks)supporting
confidence: 87%
“…It was also demonstrated that the redox imbalance induced by skin sensitizers is important in the regulation of DC functions [5,38,39,41,47,61]. Therefore, the increase in Trx-1 mRNA expression observed in .…”
Section: Discussionmentioning
confidence: 96%
“…Similarly to LPS, skin sensitizers can induce redox imbalance [38,41] that activates the cellular mechanism proposed above and responsible for the increase in Trx-1 protein levels. These data suggest that the ASK1/Nrf2/ ARE regulatory pathway could be activated by LPS and skin sensitizers in a similar way, being involved in DC maturation.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that dendritic cell maturation signals can also be provided by necrotic cell death through the release of intracellular molecules into the extracellular matrix (27,28), apoptotic cell death (29), or the induction of oxidative stress (30,31). Indeed, studies with contact sensitizers have demonstrated that small protein-reactive compounds can induce dendritic cell maturation (30,32,33) at concentrations associated with significant cell death (34).…”
mentioning
confidence: 99%